Implementasi Prosedur Audit Aset Tetap pada Perusahaan Sektor Jasa Pelayaran (Jurnal Riset Manajemen dan Akuntansi, 2025)
Fixed asset audit is one of the crucial elements in the financial statement examination process due to its material value and complex accounting treatment. This study aims to evaluate the implementation of fixed asset audit procedures by KAP DJS in a company within the maritime service sector. The method used is qualitative with a descriptive analytical approach covering the audit stages including planning, execution, and reporting. The results show that KAP DJS has applied audit procedures systematically in accordance with the Auditing Standards (SA). The fixed assets audited focused on ships and barges, which require specific testing related to existence, legality, and treatment of docking costs. However, there are limitations in the physical inspection process, which was only conducted on docked vessels, without applying alternative procedures such as verification through shipping logbooks or GPS tracking. Nonetheless, in general, the implementation of audit procedures by KAP DJS has been effective in detecting material misstatement risks and ensuring the fair presentation of fixed assets, although further segmentation is needed when testing movable assets.